Alterations of intracerebral connectivity in epilepsy patients with secondary bilateral synchrony - Hammen, T.; Reisert, M.; Juschkat, W.; Egger, K.; Urbach, H.; Zentner, J.; Beck, J.; Hamer, Hajo; Steinhoff, B. J.; Baumgartner, C.; Schulze-Bonhage, A.; Puhahn-Schmeiser, B. (Epilepsy Research, 2020)
Introduction: The aim of our study was to evaluate intracerebral network changes in epilepsy patients demonstrating secondary bilateral synchrony (SBS) in EEG by applying a new Diffusion Tensor Imaging (DTI) method using an energy-based global tracking algorithm. Materials and methods: 10 MRI negative epilepsy patients demonstrating SBS in 10–20 surface EEG were included. EEG findings were analyzed for irritative zones characterized by focal interictal epileptiform discharges (IEDs) triggering SBS. In addition, DTI including an energy-based global tracking algorithm was applied to analyze fiber tract alterations in irritative zones. To measure the deviation of a certain cortical connection in comparison to healthy controls, normalized differences of fiber tract streamline counts (SC) and their p-values were evaluated in comparison to corresponding fibers of the control group. Results: In 6 patients the irritative zone initiating SBS was located in the frontal lobe, in 3 patients in the temporal lobe and in 1 patient in the region surrounding the right central sulcus. All patients demonstrated significantly altered SC in brain lobes where the irritative zone triggering SBS was located (p ≤ 0.05). Seven out of 10 patients demonstrated SC alterations in tracts connecting brain lobes between the ipsilateral and the contralateral hemisphere (p ≤ 0.05). Conclusion: Our data demonstrate that alterations in fiber tracts in irritative zones triggering SBS are not necessarily associated with intracerebral lesions visible in high resolution MRI. Our study gives evidence that diffusion tensor imaging is a promising non-invasive additive tool for intracerebral network analyses even in MRI-negative epilepsy patients.
CRIS-Team Scopus Importer:2020-08-07
Keywords: contralateral propagation; diffusion tensor imaging; epilepsy patients; fiber tracts; intracerebral network changes; irritative zone; MRI negative; secondary bilateral synchrony; streamline counts